Isolation and Screening of Amylolytic and Proteolytic Thermophilic Bacteria from Way Panas Hot Spring, Kalianda, South Lampung - Laras Mahestri; Esti Harpeni; Agus Setyawan (Faculty of Fisheries and Marine, Universitas Riau, 2021)
Amylolytic and proteolitic activity from thermophilic bacteria have been observed from the Way Panas hot springs, Kalianda, South Lampung. This study aims to isolate and screen amylase and protease enzyme-producing thermophilic bacteria and their potential in fisheries. A total of 8 bacterial isolates were examined from the Way Panas hot spring, Kalianda. Each was cultured on selective medium for amylase and protease production. The results showed that 4 bacterial isolates were able to hydrolyze starch (A.WP.50.1, A.WP.50.1, A.WP.50.3, and A.WP.50.4) were able hydrolyze starch and no bacterial isolates had hydrolysis activity against protein. The highest activity of amylolitic was achieved by A.WP.50.4 bacteria isolate. Based on the phenotype, biochemistry assay, and 16s rDNA sequencing, the A.WP.50.4 bacteria isolate have high similarity and identified as Bacillus cereus.